Restrictions on the Application of the Ultimum Remedium Principle to Corporate Taxpayers in the Criminal Act of Using Fictitious Tax Invoices (Decision Study Number: 77/Pid.Sus/2022/PT Jmb) - sarmila karina (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the application of the ultimum remedium principle to corporate taxpayers in criminal acts involving fictitious tax invoices based on Decision Number: 77/Pid.Sus/2022/PT JMB. The research method uses a normative legal approach with case studies. The results show that the ultimum remedium principle was not fully applied to halt criminal proceedings, but rather considered in determining the severity of sanctions. The judge imposed house arrest sentences considering juridical and non-juridical aspects, including significant state losses and the defendant's good faith in returning part of the losses. The application of this principle reflects a balance between law enforcement and substantive justice.